Influence of the Calcination Atmosphere on Copper-Aluminum Catalysts for the Selective Dehydration of Glycerol - Lete Sanz, Alejandro; Lacleta, Francisco; García, Lucía; Ruiz, Joaquín; Arauzo, Jesús (Jornada de Jóvenes Investigadores del I3A, 2024)
The present work studied the influence of two atmospheres (air or N2) in the calcination step at 500 ºC on catalysts based on copper and aluminum with a 28 mol% of Cu. The catalysts were characterized and tested in gas-phase reactions for the selective dehydration of glycerol into acetol.